2017
DOI: 10.2519/jospt.2017.7079
|View full text |Cite
|
Sign up to set email alerts
|

The Responsiveness and Interpretability of the Shoulder Pain and Disability Index

Abstract: Study Design Clinical measurement study, prospective cohort design. Background Shoulder pain is a common disorder, and treatment is most often focused on a reduction of pain and functional disabilities. Several reviews have encouraged the use of the Shoulder Pain and Disability Index (SPADI) to objectify functional disability. It is important to assess the responsiveness and interpretability of the SPADI in patients seeking physical therapy treatment for their shoulder pain in a primary care setting. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Consistent with previous literature on MIC estimation, the MICs varied according to the baseline scores [19,24,64,65]. Our results showed that higher baseline scores resulted in higher MIC values.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous literature on MIC estimation, the MICs varied according to the baseline scores [19,24,64,65]. Our results showed that higher baseline scores resulted in higher MIC values.…”
Section: Discussionsupporting
confidence: 91%
“…Seven hypotheses were formulated per subscale (Table ). These hypotheses were based on previous studies assessing responsiveness and methodology guidelines by COSMIN …”
Section: Methodsmentioning
confidence: 99%
“…The total score varies between 0 and 100, a higher score indicates a higher level of pain-related disability [ 18 ]. The Dutch SPADI (SPADI-D) has shown to be valid (hypothesis testing, factor structure), reliable (internal consistency and test–retest), interpretable (measurement error, floor, and ceiling effects) and responsive, in patients with shoulder pain in primary care [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%